Solving Delay Differential Equations Using Least Square Method Based on Successive Integration Technique - A. Emimal Kanaga Pushpam, C. Kayelvizhi (Mathematical Statistician and Engineering Applications, 2023)
In this paper, least square method (LSM) based on successive integration technique is proposed for solving delay differential equations (DDEs). Continuous LSM and Discrete LSM have been presented. In this study we adopted four different orthogonal polynomials for weighted basis function. Numerical examples are considered for testing the efficiency of the proposed method. The proposed method gives results with very good accuracy. It demonstrates the reliability and efficiency of this technique for solving DDEs.